Aktivitas Promosi Wisata Kuliner Ikan Bilih Sebagai Makanan Khas Danau Singkarak Kabupaten Tanah Datar - faizah, Salsabila; Edlina, Ria (CV. ITTC INDONESIA, 2024)
The problem studied in this research is culinary tourism promotion activities for bilih fish as a typical food of Lake Singkarak in promoting and marketing bilih fish culinary tourism. Based on these problems, this research aims to describe the marketing promotion activities used by UMKMactors at the Tourism Department in carrying out promotional activities for the Ikan Bilih culinary tourism product. The research approach used is descriptive qualitative. The source of research data is the result of observations of the activities of the Tanah Datar Regency Tourism Office and UMKM actors at Lake Singkarak. Data collection was carried out using observation, interviews and documentation techniques. The theory used is IMC (integrated marketing communications). This theory was put forward to show that the Bilih Fish culinary tourism promotional activities used by Bilih Fish traders in marketing their tourism products are advertising techniques, sales promotions, personal sales